University–industry collaboration: A literature review and synthesis. Issue 4 (August 2019) - Sjöö, Karolin; Hellström, Tomas
This study applies a systematic literature review and qualitative content analysis to identify and synthesize key factors that enable collaborative innovation between industry and universities. Using a keyword search in the Web of Science database, the review identified 40 papers that were frequently cited on the topic. Results were summarized into seven main themes or central factors stimulating collaborative innovation: resources, university organization, boundary-spanning functions, collaborative experience, culture, status centrality and environmental context. This article elaborates on these 'enabling factors' and uses them to summarize a number of results from the reviewed studies regarding facilitators of collaborative innovation. The discussion focuses on how these factors relate and the extent to which they are amenable to policy intervention.